Single-Cell RNA Sequencing Reveals Peripheral Immune Cell Senescence and Inflammatory Phenotypes in Patients with Premature Ovarian Failure - Liu J; Wang L; Zhong W; Cai J; Sun Y; Li S; Li J; Liu Y; Xiong F (Journal of Inflammation Research)
Jianan Liu,1 Li Wang,2 Weijun Zhong,1 Jing Cai,3 Yan Sun,3 SongJun Li,2 Jiayi Li,4 Yanhui Liu,2 Fu Xiong1,5,6 1Department of Medical Genetics/Experimental Education/Administration Center, School of Basic Medical Sciences, Southern Medical University, Guangzhou, People’s Republic of China; 2Reproductive Medicine Department, The Third Affiliated Hospital of Shenzhen University, Shenzhen, Guangdong, People’s Republic of China; 3Reproductive Medicine Department, Dongguan Maternal and Children Health Hospital, Dongguan, Guangdong, People’s Republic of China; 4The First Clinical Medical School, Nan Fang Hospital, Southern Medical University, Guangzhou, People’s Republic of China; 5Guangdong Provincial Key Laboratory of Single Cell Technology and Application, Guangzhou, Guangdong, People’s Republic of China; 6Department of Fetal Medicine and Prenatal Diagnosis, Zhujiang Hospital, Southern Medical University, Guangzhou, People’s Republic of ChinaCorrespondence: Fu Xiong, Department of Medical Genetics/Experimental Education/Administration Center, School of Basic Medical Sciences, Southern Medical University, Guangzhou, 510515, People’s Republic of China, Email xiongfu@smu.edu.cn Yanhui Liu, Reproductive Medicine Department, The Third Affiliated Hospital of Shenzhen University, Shenzhen, 518061, People’s Republic of China, Email liuliang71215@163.comBackground: Premature Ovarian Failure (POF) is a heterogeneous syndrome characterized by ovarian dysfunction, frequently associated with autoimmune factors. The interaction between peripheral and ovarian immune signals remains unclear. Recent advancements in single-cell technology provide a unique opportunity to examine the complex peripheral immune response in POF patients at the microstructural level. This study investigates the immune microenvironment’s complexity through the interaction between peripheral and ovarian local immune responses.Methods: Peripheral blood mononuclear cells (PBMCs) were isolated from three healthy individuals and four POF patients. Single-cell RNA sequencing (scRNA-seq) was used to delineate cell clusters and identify differentially expressed genes (DEGs). Enrichment, SCENIC, and pseudo-time analyses were utilized to explore cellular phenotype diversity, regulatory patterns, and evolutionary trajectories. A POF mouse model was used for validation.Results: Seven clusters were identified and classified into two groups. POF patients exhibited increased proportions in T cells, NK cells, and B cells as well as upregulated IGLC2, GNLY, GZMB, FCGR3A, and CCL5 expressions compared to healthy controls. Monocytes, particularly non-classical monocytes, exhibited inflammatory phenotypes. CD8+ Effector T cells demonstrated increased cytotoxicity and TCR clonal expansion. The trajectory of CD8+ Effector T cells in POF patients involved the synchronous upregulation of cytotoxic-related genes and immune checkpoint molecules. Notably, CCL5, primarily produced by non-classical monocytes, emerged as a critical factor. Elevated levels of CCL5 in plasma and local ovaries, along with increased CD8+ T cell infiltration, suggested its potential role in chemotaxis and ovarian damage in POF. Validation in the POF mouse model further supported these findings.Conclusion: In summary, this study provides in-depth insights into the immune landscape of POF, revealing distinct cell populations, pathways, and signaling networks linked to the disease. These findings enhance our understanding of POF’s immunological mechanisms, contributing to the development of potential diagnostic and therapeutic strategies.Keywords: premature ovarian failure, immune microenvironment, single-cell RNA sequencing, monocytes, CD8+ effector T cells, CCL5